Assessing the accuracy of open-source digital elevation models for the geomorphological analysis of very small islands of Indonesia - Mutaqin, Bachtiar W. (Springer Science and Business Media Deutschland GmbH, 2023)
Digital elevation models (DEMs) are used for many geosciences studies; hence, their accuracy is essential. Throughout the world, there are many small islands of various sizes and densities; hence, it is important to assess the DEM accuracy on very small islands since DEMs serve as the major data source for many investigations, particularly in geomorphology, land-use planning, and disaster management. Therefore, this paper aims to validate the accuracy of an open-source Indonesian DEM (DEMNAS) in the very small islands of Karimunjawa–Indonesia. Validation was conducted by comparing elevation values from DEMNAS to the true elevation values in four very small islands in Karimunjawa, namely Cemara Besar, Cemara Kecil, Menjangan Besar, and Menjangan Kecil. The true elevation values were obtained by orthorectification of aerial imagery using a DJI Mavic Air-2 Unmanned Aerial Vehicle (UAV). The orthorectification came from ground control points (GCP) from the geodetic Global Positioning System (GPS). In the study area, fourteen GCP were erected; for more significant coverage, they were placed along the edges of the very small islands. After that, Agisoft software analyzed the images to produce a DEM using GCP orthorectification. Based on 280 sampling points, we applied a root-mean-square error (RMSE) to calculate elevation errors, and we performed the linear error 90 (LE90) calculation to judge the average errors with the 90 threshold of absolute values of discrepancies. The DEMNAS RMSE and LE90 calculation results in the Karimunjawa archipelago were 6.33 m and 10.45 m, respectively. Citing Regulation Number 15 of the Head of the Indonesian Geospatial Information Agency of 2014 concerning Technical Guidelines for Basic Map Accuracy, DEMNAS with 10.45 m LE90 can be utilized for producing geomorphological maps with scales of 1:25,000 or smaller. However, detailed geomorphological mapping of a very small island (less than 100 km2) needs better DEM data that is usually produced using aerial photogrammetry. Using UAVs for DEMs creation may benefit small island developing states (SIDS) worldwide. © 2023, The Author(s), under exclusive licence to Società Italiana di Fotogrammetria e Topografia (SIFET).